Revisionary study of the genus Gomphostemma Wall. ex Benth. (Lamiaceae) from Bangladesh - Khanam, Mahbuba; Khan, M Salar; Hassan, Md Abul (Bangladesh Journal of Plant Taxonomy, 2003)
No abstract available. Bangladesh J. Plant Taxon. 10(2): 1-10, 2003 (December)